Structural basis for hepatitis B virus restriction by a viral receptor homologue - Kaho Shionoya; Jae-Hyun Park; Toru Ekimoto; Junko S. Takeuchi; Junki Mifune; Takeshi Morita; Naito Ishimoto; Haruka Umezawa; Kenichiro Yamamoto; Chisa Kobayashi; Atsuto Kusunoki; Norimichi Nomura; et al. (Nature Communications)
Abstract Macaque restricts hepatitis B virus (HBV) infection because its receptor homologue, NTCP (mNTCP), cannot bind preS1 on viral surface. To reveal how mNTCP loses the viral receptor function, we here solve the cryo-electron microscopy structure of mNTCP. Superposing on the human NTCP (hNTCP)-preS1 complex structure shows that Arg158 of mNTCP causes steric clash to prevent preS1 from embedding onto the bile acid tunnel of NTCP. Cell-based mutation analysis confirms that only Gly158 permitted preS1 binding, in contrast to robust bile acid transport among mutations. As the second determinant, Asn86 on the extracellular surface of mNTCP shows less capacity to restrain preS1 from dynamic fluctuation than Lys86 of hNTCP, resulting in unstable preS1 binding. Additionally, presence of long-chain conjugated-bile acids in the tunnel induces steric hindrance with preS1 through their tailed-chain. This study presents structural basis in which multiple sites in mNTCP constitute a molecular barrier to strictly restrict HBV.